Technology and the Two Margins of Labor Adjustment: A New Keynesian Perspective - Francesco Furlanetto; Tommy Sveen; Lutz Weinke (Norges Bank, 2018)
Canova et al. (2010 and 2012) estimate the dynamic response of labor market variables to technological shocks. They show that investment-speci c shocks imply almost exclusively an adjustment along the intensive margin (i.e., hours worked), whereas for neutral shocks the largest share of the adjustment takes place along the extensive margin (i.e., employment). In this paper we develop a New Keynesian model featuring capital accumulation, two margins of labor adjustment and a hiring cost. The model is used to analyze a novel economic mechanism to explain that evidence.
hdl:11250/2500933
Keywords: 330; technological shocks; sticky prices; labor market; E22; E24; E32